Early Childhood Educators and Teachers in Indonesia (A survey of the Conditions of Teachers Early Childhood in 5 Major Cities of Indonesia) - Meilanie, R. Sri Martini (Universitas Negeri Semarang, 2016)
Early Childhood Educators and Teachers phenomena in Indonesia today can be said there has been no significant improvement of the quality aspect to profesian and mental readiness in carrying out the functions and duties of the principal. Regulation to improve the quality of the profession with the demands of strata S1 for early childhood educators and teachers not yet fully implemented. There are still many educators and early childhood teachers who have not reached the strata S1 moreover, educators and early childhood teachers similar (non-formal), where for educators and early childhood teachers (non-formal) is still widely managed by the PKK that basic education is still very heterogeneous. This can be confirmed by the findings of the study nearly 50% of educators and teachers have a background in high school education up to S1, even for similar early childhood educators and teachers there who have a background in primary education 6%, secondary 11%. While educators and early childhood teachers who have the educational background that does not comply with the demands of the profession at 38.6%. The above conditions are caused because of the jobs that are considered the easiest and many educators and teachers are becoming even more into early childhood teachers. Ordinary people think so educators and early childhood teachers are very easy it is expressed by 39% of respondents number, origin have a bit of a whim, can sing, clap, invited to play children and nurture and soothe the child when the petulant. Society in general has not been widely realized that early childhood is a very fundamental stage in order to form and mature children. If at this stage the process of formation and maturation of children is not optimal possibility at a later stage the child was not mature so that the process of obtaining the learning experience will be obstacles. Learning outcomes according to standards development as expected the government not be thought of educators and teachers (66.3%). What is certain early childhood educators and teachers in the field are able to make smart kid writing, numeracy and literacy needed for the provision of enrollment in primary school (49%). People still think of early childhood is not so important that the focus on learning experience is not too optimal, early childhood learning course played only later when the child in primary school. Not to mention the cultural factors that shape the mental profession of early childhood educators and teachers are still considered weak. Mental